2019
DOI: 10.3847/1538-4357/ab5790
|View full text |Cite
|
Sign up to set email alerts
|

Active Galactic Nuclei with Ultrafast Outflows Monitoring Project: The Broad-line Region of Mrk 79 as a Disk Wind

Abstract: We developed a spectroscopic monitoring project to investigate the kinematics of the broad-line region (BLR) in active galactic nuclei (AGN) with ultra-fast outflows (UFOs). Mrk 79 is a radio-quiet AGN with UFOs and warm absorbers, had been monitored by three reverberation mapping (RM) campaigns, but its BLR kinematics is not understood yet. In this paper, we report the results from a new RM-campaign of Mrk 79, which was undertaken by Lijiang 2.4-m telescope. Mrk 79 is seeming to come out the faint state, the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
28
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 106 publications
1
28
1
Order By: Relevance
“…In some degree, this is consistent with the previous finding from NGC 5548 that the BLR size follows the varying optical luminosity at 5100 Å (Lu et al 2016), but Lu et al (2016) extra found that the variations of the BLR size lag behind the varying optical luminosity. Lu et al (2019a) also found that the BLR size of Mrk 79 is significantly smaller in the low-luminosity state than normal-luminosity state. Like NGC 5548, developing long-term RM campaign for more famous AGNs would help us to understand the variations of BLR with the varying ionizing radiation.…”
mentioning
confidence: 75%
See 3 more Smart Citations
“…In some degree, this is consistent with the previous finding from NGC 5548 that the BLR size follows the varying optical luminosity at 5100 Å (Lu et al 2016), but Lu et al (2016) extra found that the variations of the BLR size lag behind the varying optical luminosity. Lu et al (2019a) also found that the BLR size of Mrk 79 is significantly smaller in the low-luminosity state than normal-luminosity state. Like NGC 5548, developing long-term RM campaign for more famous AGNs would help us to understand the variations of BLR with the varying ionizing radiation.…”
mentioning
confidence: 75%
“…During the long slit spectroscopy, we oriented long slit to take the spectra of AGN and a nearby non-varying comparison star simultaneously, this observation method was described in detail by Maoz et al (1990) and Kaspi et al (2000). The comparison star as a reference standard can provide a high-precision flux calibration (Lu et al 2016(Lu et al , 2019a. In addition, the spectra of comparison star can be used to correct the telluric absorption lines of the target spectrum (Lu et al 2021).…”
Section: Spectroscopic Observationmentioning
confidence: 99%
See 2 more Smart Citations
“…Here, the AGN is a structure mostly illuminated by a bright accretion disk around a supermassive black hole (SMBH). Additional contributions to luminosity and extinction can come from other components, such as a disk wind (Konigl & Kartje 1994;Murray et al 1995;Elvis 2000;Proga et al 2000;Long & Knigge 2002;Proga & Kallman 2004;Kollatschny & Zetzl 2013;Higginbottom et al 2013;Galianni & Horne 2013;Laor & Davis 2014;Higginbottom et al 2014;Matthews et al 2015Matthews et al , 2017Mangham et al 2017;Nomura & Ohsuga 2017;Lu et al 2019;Mizumoto et al 2019) or a warped disk (Petterson 1977;Papaloizou & Lin 1995;Pringle 1997;Nayakshin 2005;Ulubay-Siddiki et al 2009;Wu et al 2010;King et al 2013;Matthews et al 2020). The luminous central engine is then obscured by an axisymmetric dusty molecular 'torus', classically a static structure whose thickness is supported by infrared radiation pressure (Pier & Krolik 1992;Granato & Danese 1994;Krolik 2007;Shi & Krolik 2008).…”
Section: Introductionmentioning
confidence: 99%